'Brexit means Brexit': Theresa May and post-referendum British politics. Issue 1 (April 2018) - Allen, Nicholas
Abstract Theresa May became prime minister in July 2016 as a direct result of the Brexit referendum. This article examines her political inheritance and leadership in the immediate wake of the vote. It analyses the factors that led to her victory in the ensuing Tory leadership contest and explores both the main challenges that confronted her and the main features of her response to them. During her first 9 months in office, May gave effect to the referendum, defined Brexit as entailing Britain's removal from membership of the European Union's single market and customs union and sought to reposition her party. However, her failure to secure a majority in the 2017 general election gravely weakened her authority and the viability of her plans. At time of writing, it is unclear how much longer her premiership can last or if she will be able to exercise effective leadership over Brexit.